Penguatan Peran Kader dalam Mendukung Komunikasi Kesehatan Reproduksi antara Orang Tua dan Remaja melalui Program Edukasi Komunitas - Tanjung Anitasari Indah Kusumaningrum; Wardhatul Livia; Yuli Kusumawati; Sri Indra Kurnia; Eny Purwandari; Rochmadina Suci Bestari; Ahmada Auliya Rahman; Alya Tsurrayya; Fairus El Had; Munifatu Rodiyah (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to strengthen the role of community health cadres in enhancing reproductive health communication between parents and adolescents. The program was conducted at the Semanggi Village Office, Surakarta, and involved 31 community health cadres representing each neighborhood unit (Rukun Tetangga [RT]). The program was implemented through educational sessions and interactive counseling. Program outcomes were evaluated using a structured questionnaire, and the data were analyzed descriptively. The results demonstrated an improvement in the cadres' knowledge of reproductive health communication, with the mean score increasing from 8.8 in the pre-intervention assessment to 9.2 in the post-intervention assessment. These findings indicate greater consistency in participants' understanding after receiving the educational intervention. Furthermore, the program strengthened the capacity of community health cadres to serve as agents of change at the family and community levels, thereby fostering more effective and sustainable reproductive health communication between parents and adolescents and supporting efforts to prevent adolescent reproductive health problems within the community.